Mejoramiento Tecnológico en la elaboración de de chancaca y evaluación de empaques en el almacenamiento” - Grández Armas, Lincoln (2003)
This work of research, was carried out in the laboratories of analysis and composition of agro-industrial products (ANACOMPA), and agro-industrial products technology not food (TEPANAL) of the Faculty of engineering Agroindustrial of the National University of San Martín and in the processing plant of molasses of the Agroindustrial San Pedro S.A.C. company which is located in San José de Sisa , Province of the Golden in the Region San Martín. This research determined the technological parameters of the process of elaboration of the molasses, in order to obtain a good quality product and its stability in storage through a suitable packagThe work was developed in three stages: 1) study of pre-cleaning of cane juice using different quantities and concentrations of caballousa (Triumfetta semitriloba l.), 2) study of clarification and concentration of the juice to obtain the molasses and 3) evaluation of three o-rings during the to the...